2020
DOI: 10.3389/fonc.2019.01574
|View full text |Cite
|
Sign up to set email alerts
|

UBE2C Overexpression Aggravates Patient Outcome by Promoting Estrogen-Dependent/Independent Cell Proliferation in Early Hormone Receptor-Positive and HER2-Negative Breast Cancer

Abstract: We previously showed that UBE2C mRNA expression is significantly associated with poor prognosis only in patients with hormone receptor (HR)+/human epidermal growth factor receptor 2 (HER2)-breast cancer. In this study, we further reanalyzed the correlation between UBE2C mRNA expression and clinical outcomes in patients with HR+/HER2-breast cancer, and we investigated the molecular mechanism underlying the role of UBE2C modulation in disease progression in this subgroup of patients. Univariate and multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…For example, UBE2C is involved in the tumorigenesis of colorectal cancer [23] and non-small cell lung cancer (NSCLC) [24]. UBE2C is highly expressed in breast microcalcification lesions [25] and its overexpression is correlated with relapse in early HR + /HER2 − breast cancer patients [9]. UBE2C expression is elevated and predicts poor prognosis in hepatocellular carcinoma, esophageal squamous cell carcinoma and intestinal-type gastric cancer [14,26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, UBE2C is involved in the tumorigenesis of colorectal cancer [23] and non-small cell lung cancer (NSCLC) [24]. UBE2C is highly expressed in breast microcalcification lesions [25] and its overexpression is correlated with relapse in early HR + /HER2 − breast cancer patients [9]. UBE2C expression is elevated and predicts poor prognosis in hepatocellular carcinoma, esophageal squamous cell carcinoma and intestinal-type gastric cancer [14,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…UBE2C overexpression causes loss of mitotic spindle checkpoint activity and genomic stability [ 8 ]. The expression level of UBE2C is very high in various human cancers, such as breast cancer [ 9 ], ovarian cancer [ 10 ], head and neck squamous cell carcinoma (HNSCC) [ 11 ] and melanoma [ 12 ], suggesting that UBE2C is associated with tumorigenesis. Moreover, overexpression of UBE2C is correlated with tumor progression [ 13 ], so it acts as a potential prognostic/diagnostic biomarker in various types of tumors [ 11 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…UBE2T and UBE2C have been previously associated with cancer progression and poor outcome in several solid tumors, although genomic evidence in BC is recent and limited [32][33][34][35][36]. Consistently, in vitro functional experiments in ER positive HER2 negative BC cells showed that UBE2C expression is a tumorigenic factor, that it is regulated by estrogen through direct binding to the UBE2C promoter region, and that its overexpression leads to estrogen-independent growth [37]. Moreover, UBE2C depletion markedly increased the cytotoxicity of letrozole, tamoxifen, doxorubicin, and the sensitivity to radiation therapy in multiple BC cell lines [37,38].…”
Section: Discussionmentioning
confidence: 92%
“…Ubiquitin-conjugating enzyme E2 C (UBE2C) has been illustrated to facilitate proliferation, survival, invasion, and EMT in cancer [ 187 , 222 , 223 ]. For example, UBE2C can stimulate EMT process by activating Wnt/β-catenin signaling, PI3K/Akt signaling, and the level of Zinc finger E-Box-binding homeobox 1 (ZEB1) and ZEB2 [ 187 , 223 ].…”
Section: Mirnas Suppressing Anoikis Resistance and Anchorage-indepmentioning
confidence: 99%